1989
DOI: 10.1128/aac.33.8.1222
|View full text |Cite
|
Sign up to set email alerts
|

Sodium status influences chronic amphotericin B nephrotoxicity in rats

Abstract: The nephrotoxic potential of amphotericin B (5 mg/kg per day intraperitoneally for 3 weeks) has been investigated in salt-depleted, normal-salt, and salt-loaded rats. In salt-depleted rats, amphotericin B decreased creatinine clearance linearly with time, with an 85% reduction by week 3. In contrast, in normal-salt rats creatinine clearance was decreased but to a lesser extent at week 2 and 3, and in salt-loaded rats creatinine clearance did not change for 2 weeks and was decreased by 43% at week 3. All rats i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…3). The ability of sodium chloride alone to reduce the amphotericin B-induced decrease in creatinine clearance confirms previous observations that supplementation with sodium chloride attenuates the nephrotoxic effect of amphotericin B (14). The combination of flucytosine and sodium chloride had no further additive renoprotective effects.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…3). The ability of sodium chloride alone to reduce the amphotericin B-induced decrease in creatinine clearance confirms previous observations that supplementation with sodium chloride attenuates the nephrotoxic effect of amphotericin B (14). The combination of flucytosine and sodium chloride had no further additive renoprotective effects.…”
Section: Resultssupporting
confidence: 75%
“…We have previously shown that levels of amphotericin B in renal tissue during chronic therapy are influenced by salt status. Despite equivalent steady-state trough plasma levels, levels in renal tissue were higher in salt-depleted rats than in salt-loaded rats (14). Furthermore, there was a significant association between the level in tissue and the reduction in creatinine clearance.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In chronic models of nephrotoxicity in the rat, salt loading attenuates the decreases in GFR induced by amphotericin B, while salt depletion potentiates them (16,28). In addition, there are hemodynamic changes similar to those observed after acute infusions of the drug (28).…”
mentioning
confidence: 51%
“…Both the slow infusion of the antibiotic (45,54) and the administration of the drug on alternate days lower the incidence of nephrotoxicity (32). More recently, sodium loading of the organism which can interfere with the tubuloglomerular feedback response has been shown to reduce the hemodynamic problems associated with antibiotic therapy (2,8,9,(22)(23)(24)(25)42). Another approach to decrease AmB nephrotoxicity consists of acting either on the drug itself to obtain less toxic AmB derivatives or on the galenical preparation of the drug.…”
Section: Discussionmentioning
confidence: 99%